Sistem Pendukung Keputusan Pembelian, Penjualan, dan Pengelolaan Stok Barang Dengan Metode Fuzzy - Suhindar, Christian; Christianti, Meliana (Zenit, 2012)
The application made is a decision support system to determine the best suppliers based on delivery time and payment terms as well as determining the recommended items to increase the stock. The application is web-based with the PHP programming language and Fuzzy methods Tahani model. The results of the implementation of  this  application  consists of six main modules, namely Purchases, Sales, Stock, User, Supplier and Decision Support Systems. In the purchase module, there are three  parts: purchasing, goods receipt, and billing. Purchasing module is a log from transaction of goods order that has been made to suppliers, whereas the goods receipt describes the goods  received  from  suppliers based on the previous reservation, and billing is the recording data of payment based on the goods that have been received. Sales module is the management of sales data. Stock is the master data items management. The users and suppliers module contains the data management user application and Mustika Sport supplier. Decision support system module is divided into two parts, namely the addition of stock recommendations based on the amount of goods bought and sold, and the determination of the best suppliers based on payment terms and delivery time.  Keywords:  best supplier, decision support systems, fuzzy, recommended products.